2017
DOI: 10.17795/zjrms-5809
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dialectical Behavior Therapy on Stress, Resilience and Coping Strategies in Irritable Bowel Syndrome Patients

Abstract: Background: Irritable bowel syndrome (IBS) is the most common gastrointestinal disorder that have considerable psychological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, Ringstorm et al used a semi-structured interview design to allow participants to share their personal experiences with a diagnostic workup [ 55 ]. Furthermore, the remaining two studies provided no direct measure of resilience; one used the Lang and Goulet Hardiness Scale (LGHS) and the other the Pain Catastrophizing Scale (PCS) to assess resilience’s actual ability to adapt to symptoms of the disease [ 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Ringstorm et al used a semi-structured interview design to allow participants to share their personal experiences with a diagnostic workup [ 55 ]. Furthermore, the remaining two studies provided no direct measure of resilience; one used the Lang and Goulet Hardiness Scale (LGHS) and the other the Pain Catastrophizing Scale (PCS) to assess resilience’s actual ability to adapt to symptoms of the disease [ 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A quasi-experimental study, which included two intervention and control groups, conducted by Haghayegh et al, aimed to determine the efficacy of dialectical behavioral therapy (DBT) on resilience in IBS and showed no significant difference between groups. However, despite no significant difference between the groups, the increase in resilience in the DBT group was greater than in the control group [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that dialectical behavioral therapy can be used as effective psychotherapy to improve the psychological status of patients with irritable bowel syndrome. [ 36 ] Orive et al . indicated that adding psychotherapy to the medical treatment for patients with dyspepsia significantly improved the short-term outcomes in these patients and could have long-lasting effects.…”
Section: Discussionmentioning
confidence: 99%